Financial control as a category of financial relations in public governance - V.V. Voitenko (Економіка, управління та адміністрування)
It is determined that, first of all, financial control implies an obligatory existence of subordination relations and rules that must be monitored irrespective of the sphere of financial relations (public financial relations, private financial relations, household finances, etc.); secondly, finance, as an economic category, in the performance of their functions involves the creation of rules that would regulate the processes of formation, distribution and use of financial resources, as well as determine the possibility of influencing the behavior of business entities by the owner of these resources. Since these rules are not objective and human-created, compliance with them must be monitored, their executors have the ability not to comply with these rules, to change them for their own benefit, etc. It is stated that financial control is a multiform and complicated financial category, the essence of which cannot be limited with practical activity or information system. It permeates all aspects of financial relationships. The purpose, objectives and methods of exercising financial control may vary depending on the will of the owners of financial resources, but the nature and functions of financial control remain unchanged. Therefore, financial control as a financial category must be considered through a set of characteristics that should reveal all the diversity of its essence, comprehensively reflect and comprehensively cover all aspects of its manifestation. It is substantiated that the essence of financial control as a category of financial relations in the system of public administration is revealed through a set of its characteristics, which represent financial control as an area of scientific and specialized knowledge, as an element of the management system, as a special type of practical activity and as an information system used for the purpose of management.